(untitled) (Journal of the College of Basic Education, 2026)
There is no doubt that phonological studies have not yet fully established themselves, particularly with regard to non-syntactic (embroidered) phonemes. They are subject to various opinions, as well as calls for better exploitation of these phonemes in semantic analysis at various levels. This study seeks to shed light on the terms introduced into the scope of these phonemes: (sound segment), (joint), and (length), and to clarify the function of syllables. It also explores the impact of each of the phonemes (joint) and (length) in linguistic contexts, with applications to selected examples from the Holy Quran to demonstrate their impact more clearly.